Clinical spectrum and management of anterior scleritis: case reports - Dominika Ördögh; Lilla Smeller; Dóra Júlia Szabó; Nicolette Sohár (Therapeutic Advances in Ophthalmology)
Scleritis is a rare, potentially sight-threatening, painful eye disease. Based on its anatomical involvement, it can be categorized as anterior and posterior scleritis. There are several possible causes, among which infectious and noninfectious origins should be considered. From the therapeutic aspect, it is important to clarify the infectious origin, to provide target treatment, or to identify the possible underlying autoimmune disease. Corticosteroid therapy is considered to be the basis for the stepwise treatment of scleritis. In this article, we describe the management of three patients (investigations, stepwise approach of therapy, and treatment difficulties) who developed three different types of scleritis: anterior non-necrotizing scleritis, anterior necrotizing scleritis, and scleromalacia perforans. The differential diagnosis of scleritis and its management after diagnosis pose difficulties in clinical practice. In general, the therapeutic approach is based on the principle of early and individualized treatment, which depends on the nature and severity of the patient’s inflammatory eye disease and the presence or absence of associated systemic diseases.